The 14th Dalai Lama - Buddha of Compassion - Aravinda Anantharaman (Puffin Books, 2011)
A biography of the current Dalai Lama, Tenzin Gyatso, discussing the history of Tibet and the role of the Buddhist leader in this country's spiritual and political life.
Keywords: Biography -- Biography